(untitled) (Social Inquiry: Journal of Social Science Research, 2023)
Federalisation is one of the leading political setups for the participatory involvement of all citizens in and accountability for governance; it generally offers numerous opportunities to engage in planning, policy-making, decision-making, and implementation in development initiatives and social movements. On the one hand, Nepal has a youth population, and youths are considered both products and producers of the settings in which they engage. These reciprocal processes provide a basis for self-development and others in the community. On the other hand, not much effort has been put into enhancing the youth’s capacity for meaningful participation in the development process, especially in the new federal setup. Given the background, this paper presents a critical reflection of planners and decision-makers on policies and programmes related to youth, economic empowerment of young women and youth participation in the planning process at state and local levels. Data were collected from five local governments focusing on all planning levels, from Tole consultation to Ward Assembly to Rural Municipality/Municipality to State and Federal levels. Primary data were collected at the grassroots level, where the perspective of youths, especially those from marginalised groups, about their involvement in planning processes, was captured through eight focused group discussions. Also, eight key informants, at least two elected representatives, were interviewed from the same study area.